Pengaruh Metode Cooperative Learning Teknik Jigsaw Terhadap Prestasi Belajar Mahasiswa - Adiwibowo, Lili Adi (INVOTEC, 2010)
This study is aimed to know the description of Cooperative Learning Methods Jigsaw Techniques and its influence on Student Learning Achievement of the student in Economic Education Program 2006, Faculty of Social Sciences Universitas Pendidikan Indonesia, Bandung. This study is a descriptive verification study with explanatory survey method and cross sectional method based on time period. The data are presented inÂ  primary and secondary data with the data collectted through observation, library research, and questionnaire. The analysis technique is regression analysis with SPSS computer software as the tool 12. Based on the findings obtained by statistical tests shows that there is a positive influence of Cooperative Learning Methods Jigsaw Techniques with studentsâ€™ Learning Achievement. It can be concluded that achievement is influenced by the Method of Cooperative Learning Jigsaw Technique.